The role of business in the development of the welfare state and labor markets in Germany: containing social reforms - Paster, Thomas (London, 2011)
"This book assesses the role of employers in the development of welfare state and labour market institutions. Building on an in-depth analysis of Germany, a market economy known to often provide economic benefits to firms, this book explores one of the most contested issues in the comparative and historical literature on the welfare state. In a departure from existing employer-centered explanations, the author applies new empirical data to contend that the variation in acceptance of social reform depends more on changes in the types of political challenges faced by employers, than on changes in the type of institutions considered economically beneficial. Covering major reforms spanning more than a century of institutional development in unemployment insurance, accident insurance, pensions, collective bargaining, and codetermination, this book argues that employers support social policy as a means to contain political outcomes that would have been worse, including labour unrest and more radical reform plans. Using new and controversial findings on the role of employers in welfare state development, this book considers the conditions for a peaceful coexistence of a generous welfare state and the business world."